A case of bilateral temporal lobe agenesis. Issue 7 (July 1981) - Lang, C; Lehrl, S; Huk, W
Abstract : A 76-year-old man with bilateral temporal lobe agenesis producing clinical features resembling the Robinson syndrome is described. The malformation was discovered during a routine CT examination after the appearance of a homonymous visual field defect. The patient was examined by (neuro) psychological testing. The findings are compared with other reported cases and discussed with regard to cerebral localisation.